The Failure of Technology Utilization in the Era of Digital Education: A Study at the MTs of the Kandepag Project, Medan City - Ginting, Yemmi Sofia; Khairunnisa Sitompul; Wafiq Nurhalizah; Suci Dahlya Narpila (Yayasan Bayt Shufiya Nusantara, 2025)
This study aims to describe the condition of MTs Kandepag in utilizing technology in the learning process. The method used is a field study by observing the condition of the school directly, starting from physical facilities to the application of technology in teaching and learning activities. Primary data is obtained through field records and documentation that records actual conditions in the field. Data analysis was carried out using data triangulation to ensure the validity of the findings, which were naturally outlined based on the results of direct observations. The findings of the study show that MTs Kandepag faces several challenges in the use of technology, including limited funds, lack of technology use, and lack of attention from the government. This study concludes that to increase the effectiveness of technology utilization in schools, it is necessary to make maximum efforts in providing facilities, improving teacher skills, and strengthening support from the government and the community.